2015
DOI: 10.1038/nri.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in depression: from evolutionary imperative to modern treatment target

Abstract: Crosstalk between inflammatory pathways and neurocircuits in the brain can lead to behavioural responses, such as avoidance and alarm, that are likely to have provided early humans with an evolutionary advantage in their interactions with pathogens and predators. However, in modern times, such interactions between inflammation and the brain appear to drive the development of depression and may contribute to non-responsiveness to current antidepressant therapies. Recent data have elucidated the mechanisms by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

57
1,993
3
49

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,704 publications
(2,102 citation statements)
references
References 130 publications
57
1,993
3
49
Order By: Relevance
“…There is already some evidence that anti‐inflammatory drugs can have antidepressant efficacy 32. Our results are compatible with the mechanistic interpretation that this may be at least partly attributable to the effects of anti‐inflammatory drugs on “normalization” of an inflammation‐induced bias in tryptophan and kynurenine metabolism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is already some evidence that anti‐inflammatory drugs can have antidepressant efficacy 32. Our results are compatible with the mechanistic interpretation that this may be at least partly attributable to the effects of anti‐inflammatory drugs on “normalization” of an inflammation‐induced bias in tryptophan and kynurenine metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…The anti‐inflammatory activity of COX inhibitors is thought to depend on preventing inducible prostaglandin production, which can also act in an autocrine manner in macrophages through inducible prostaglandin receptors 25. Both COX‐inhibiting and TNFα‐inhibiting drugs have been shown to have some antidepressant and anxiolytic effects in patients with psychologic symptoms in the context of medical inflammatory disorders 32. Synthetic glucocorticoids, such as prednisolone, are amongst the most commonly prescribed anti‐inflammatory agents, and act by inducing multiple feedback repressors of inflammation, including IκB and DUSP1 33.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that psychological and/or acute intense stressor exposure in the absence of overt tissue damage can evoke a detectable local and systemic sterile inflammatory response and that DAMPs may have a (Fleshner, 2013;Frank et al, 2015b;Maslanik et al, 2013;Miller et al, 2015).…”
Section: Stress Damps and Sterile Inflammationmentioning
confidence: 99%
“…Specifically, patients with depression had increased expression of NLRP3 and caspase-1 in peripheral blood mononuclear cells (Alcocer-Gomez et al (2014b)). Thus, sterile inflammation mediated by DAMPs and the inflammasome and evoked after exposure to psychological stressors may have a role in the pathogenesis of MDDs and other psychopathologies (Alcocer-Gomez and Cordero, 2014a; Kessler, 1997;Miller et al, 2015).…”
Section: Stress Damps and Sterile Inflammationmentioning
confidence: 99%
See 1 more Smart Citation